Best Answer

what is the solution of x-5y=10 and 2x-10y=20

Study guides

☆☆

Q: Help me solve this equation by substitution. x-5y equals 10 2x-10y equals 20?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

To solve the following equation by substitution, we need to have the equal sign. This will help us group the knowns and the unknowns.

what does the equation equal? if it equals zero: 0= 3x(4-11) 0=3x(-7) 0=3x 0=x if the equation doesn't equal anything, it means it's just an expression meaning you can't solve for x, you can only reduce (and this equation is already reduced). if the equation equals y, you need another equation and use either substitution or elimination to solve for x.

Algebraic equations with two variables will need two equations to be able to solve it. Then, you can solve it with either substitution, adding/subtracting them together, or graphing! Those are the basic steps... For example: An instance of substitution: 2x + 1 = y + 2 x + y = 3 You could isolate y in the second equation to equal y = 3-x. Then in the first equation, substitute y with what it equals to 2x + 1 = 3-x+2 Then you can solve for x!

George saves nickels and dimes for tolls. If he has 8 coins worth $2.60,how many are nickels and how many are dimes? Answer this question by using system of equation.

Solve the following equation for A : 2A/3 = 8 + 4A

Related questions

You cant solve it unless it is an equation. To be an equation it must have an equals sign.

x+y=5

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

You'd need another equation to sub in

-2

by elimination,substitution or through the matrix method.

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

To solve the following equation by substitution, we need to have the equal sign. This will help us group the knowns and the unknowns.

From first equation: y = 5 - 5xSubstitute for y in second equation: 3x + 10 - 10x = 3ie -7x = -7ie x = 1 and y = 0

From second equation: y = 8 + 2xSubstitute for y in first equation: 3x + 16 + 4x = 2ie 7x = -14ie x = -2 and y = 4

It is not an equation if it does not have an equals sign. You could simplify it but not solve it.

You use substitution when you can solve for one variable in terms of the others. By substituting, you remove one variable from the equation, which can then be solved. Once you solve for one variable, you can use substitution to find the other.

People also asked

Featured Questions